Research title: Analysis of reading books for the primary stage in light of cognitive economics skills (Journal of the College of Basic Education, 2025)
The research mainly aims to identify the percentage of cognitiveeconomy skills included in the Arabic reading book for the fifth grade of primary school. The sample included the topics of the Arabic reading book for the fifth grade, except for the introduction and the content list, and it amounted to (57) topics. The researcher used the "descriptive approach" and relied on a questionnaire as a tool to obtain the necessary data to achieve the goal of the research through (40 skills) within (7 areas). The results indicate that most of the skills in the fields (mental development, cognitive, communication, and social) were achieved, and half of the skills (evaluation field) were not achieved, while all the skills of the two fields (economic, technological) were not achieved in the Arabic reading book for the fifth grade of primary school.Accordingly, the researcher recommended reconsideration by curriculum developers in terms of achieving balance in including knowledge economy skills in the Arabic reading book for the fifth grade of primary school, and benefiting from studies and research in developing Arabic language books for the primary stage. She suggested conducting similar studies on other methodological books for other levels of study in light of cognitive economics skills.